EFEKTIVITAS MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMK NEGERI 1 ANGKOLA TIMUR - Harahap, Desmiati; Harahap, Muhammad Syahril; Ardiana, Nunik (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2026)
Students pay less attention to the teacher during the learning process because students find it difficult to understand the learning material, especially in mathematics. The purpose of this study was to determine the effectiveness of the contextual learning model on students' mathematical problem-solving abilities on the material of two-variable linear equation systems in Class X of SMK Negeri 1 Angkola Timur. The type of research used by the researcher is quantitative research. In this study, the researcher used the True-Experienced Design design with the One Group Pretest and Posttest Design type. The population was all students of Class X at SMK Negeri 1 Angkola Timur consisting of 6 classes totaling 92 students. Based on the data analysis, the researcher drew conclusions based on the results of data collection, there was an effectiveness of the contextual learning model on the material of two-variable linear equation systems on students' mathematical problem-solving abilities. This is evidenced by the results of the paired sample test that has been conducted in the experimental class. It can be concluded that H0 in the experimental class is rejected and Ha is accepted because the sig value (2-tailed) in the experimental class is 0.00 less than 0.05. Furthermore, based on inferential statistics using the pair sample t-test, (SPSS version 27), the results show a significance value of less than 0.05 (0.000 < 0.05). This means that the constructivism learning model is effectively used for the mathematical problem solving abilities of class X students of SMK Negeri 1 Angkola Timur.